2016
DOI: 10.1177/0192512116641815
|View full text |Cite
|
Sign up to set email alerts
|

Integrating participatory institutions into the traditional representative and bureaucratic model of public governance

Abstract: Does more citizen participation necessarily improve the democratic quality and/or the effectiveness of government? What forms of participation have the potential to accomplish these goals? And, more important, how can these participatory mechanisms be integrated into traditional representative and bureaucratic governance practices, in order to grasp this potential? We discuss these questions in the article, building on theories and empirical evidence provided by both political science and public administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…What the case of TMJC also teaches us, is that putting effective forms of participation into practice goes beyond implementing programs and mechanisms such as the Participatory Budget. Rather it requires a long-term commitment from public authorities and local communities to create truly democratic and representative platforms, in order to uphold dialogue and negotiation between different interested parts (Bandeira and Ferraro 2013). Mere public endorsement of a community's initiative and the traditional governmental formats of participatory decision-making do not automatically lead to equitable and just results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…What the case of TMJC also teaches us, is that putting effective forms of participation into practice goes beyond implementing programs and mechanisms such as the Participatory Budget. Rather it requires a long-term commitment from public authorities and local communities to create truly democratic and representative platforms, in order to uphold dialogue and negotiation between different interested parts (Bandeira and Ferraro 2013). Mere public endorsement of a community's initiative and the traditional governmental formats of participatory decision-making do not automatically lead to equitable and just results.…”
Section: Discussionmentioning
confidence: 99%
“…Mere public endorsement of a community's initiative and the traditional governmental formats of participatory decision-making do not automatically lead to equitable and just results. Although effective participation makes decision-making more complex -since it involves the recognition and conciliation of various spatial practices, identifications and forms of belonging and is likely to induce conflict -a productive use of heterogeneity and diversity is key since urban places and communities are also intrinsically diverse (Curry 2012;Inch 2012;Bandeira and Ferraro 2013). In this particular case, the strength and effectiveness of the 4 Crescente community group to make its voice heard lays in its horizontal nature and structure as knowledge exchange platform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a practice it has been around since the 1970s, and many studies have been conducted to evaluate its impact on different aspects of human life. Based on many evaluations, scholars have concluded that the approach has contributed to promote an inclusive and cohesive society, construct strong citizenship, strengthen the practice of participation, and develop a responsive and accountable state (Bandeira and Ferraro, 2017; Gaventa and Barrett, 2012; Mansuri and Rao, 2013; Speer, 2012). With regards to the impact on women's empowerment in Indonesia, some studies have shown that the approach has had a positive impact on women's practical interest, mostly their well-being (women's health, education, and income) (Akatiga, 2010; Beard & Cartmill, 2007; Jakimow, 2017; Scanlon, 2012; Wong, 2002).…”
Section: Participatory Governance and Gender Policies In The New Deve...mentioning
confidence: 99%
“…However, even where there are deliberate attempts to open up processes, as with petitions systems, publication of draft bills and more open calls for evidence, significant challenges remain, including in relation to existing disparities of power and resources (for example, Barnes et al ., 2007), fairness of process and the management of expectations (Bochel, 2016), as well as the potential difficulties associated with balancing attempts to develop more participative forms of democracy alongside traditional representative democracy (for example, Bandeira and Ferraro, 2017; Bochel and Bochel, 2017). It is therefore not surprising that there have been concerns expressed that parliamentary committees continue to a large extent to listen to the ‘usual suspects’ (for example, Halpin et al ., 2012; Liaison Committee, 2012; Pedersen et al ., 2015), who also arguably have better access than other interests through other parts of the political and policy-making processes (McGarvey and Cairney, 2008).…”
Section: Committees and Witness Diversitymentioning
confidence: 99%